Keracunan coklat pada anjing: manajemen terapi dan pencegahan - Yanuartono Yanuartono; Alfarisa - Nururrozi; Soedarmanto - Indarjulianto; Slamet - Raharjo; Hary - Purnamaningsih; Nurman - Haribowo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Chocolate poisoning has long been recognized as a common cause mostly in dogs, although many species are susceptible. Contributing factors include indiscriminate eating habits and readily available sources of chocolate. In general, the poisoning resulted from a lack of public knowledge of the health hazard to dogs that may be imposed by these products.Chocolate is derived from the seeds of the plant Theobroma cacao, and the main toxic components are the methylxanthine alkaloids theobromine and caffeine, causing gastrointestinal, cardiovascular and central nervous signs. Diagnosis is based on history of exposure, along with clinical signs. Amphetamine or cocaine toxicosis, and ingestion of antihistamines, antidepressants, or other CNS stimulants should be considered in the differential diagnosis. Stabilization of symptomatic animals is a priority in treating chocolate toxicosis. Although there is no specific antidote, supportive management includes induction of vomiting and administration of activated charcoal, oxygen, and intravenous fluids. Preventing exposure is the key to reducing the incidence of these poisoning episodes. Therefore, it is important to increase the knowledge of dogs owners with regard to foodstuffs that must not be fed to dogs and should be stored outside their reach.